2021
DOI: 10.1098/rsta.2020.0116
|View full text |Cite
|
Sign up to set email alerts
|

Nutations in growing plant shoots as a morphoelastic flutter instability

Abstract: Growing plant shoots exhibit spontaneous oscillations that Darwin observed, and termed ‘circumnutations’. Recently, they have received renewed attention for the design and optimal actuation of bioinspired robotic devices. We discuss a possible interpretation of these spontaneous oscillations as a Hopf-type bifurcation in a growing morphoelastic rod. Using a three-dimensional model and numerical simulations, we analyse the salient features of this flutter-like phenomenon (e.g. the characteristic period of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…According to a prevailing theory for the interpretation of circumnutations, such oscillatory movements are of exogenous nature and arise from the over-compensatory response of the plant to the changing orientation of its gravisensory apparatus relative to the Earth's gravity [120][121][122][123][124]. Recently, mechanical models based on morphoelastic rods theory [125] have been proposed and tested to support this hypothesis [126][127][128]. Specifically, it was shown that nutations in growing plant shoots may be interpreted as spontaneous oscillations caused by a flutter instability (a Hopf bifurcation) in a growing elastic system subject to gravity loading, while sensing and actively responding to external stimuli.…”
Section: (B) Spontaneous Motion In Growing Plantsmentioning
confidence: 99%
“…According to a prevailing theory for the interpretation of circumnutations, such oscillatory movements are of exogenous nature and arise from the over-compensatory response of the plant to the changing orientation of its gravisensory apparatus relative to the Earth's gravity [120][121][122][123][124]. Recently, mechanical models based on morphoelastic rods theory [125] have been proposed and tested to support this hypothesis [126][127][128]. Specifically, it was shown that nutations in growing plant shoots may be interpreted as spontaneous oscillations caused by a flutter instability (a Hopf bifurcation) in a growing elastic system subject to gravity loading, while sensing and actively responding to external stimuli.…”
Section: (B) Spontaneous Motion In Growing Plantsmentioning
confidence: 99%